Non-pharmacologic Prevention of Acute Exacerbation Chronic Obstructive Pulmonary Disease - Joon Young Choi (Tuberculosis and Respiratory Diseases, 2025)
Chronic obstructive pulmonary disease (COPD) is a major global health issue, as acute exacerbation COPD (AECOPD) significantly worsens outcomes and increases healthcare burden. This review explores non-pharmacologic strategies to prevent AECOPD. Pulmonary rehabilitation consistently demonstrates its effectiveness in reducing exacerbations and mortality, while improving exercise capacity and the quality of life. Lung volume reduction, through both surgical and bronchoscopic methods, has shown promise in select patient groups, leading to improved lung function and reduced exacerbation risk. Smoking cessation remains a critical intervention, while the role of electronic cigarettes remains debatable; some evidence suggests they may help patients unable to quit tobacco smoking. Vitamin D supplementation has shown potential in reducing exacerbations, particularly in patients with severe deficiency, though conflicting results warrant further research. Furthermore, shielding measures, like mask-wearing and social distancing, have gained attention during the coronavirus disease 2019 (COVID-19) pandemic for their role in reducing exacerbation risk. Lastly, vaccination, diet and nutrition, and non-invasive ventilation may be important to prevent AECOPD. These non-pharmacologic approaches should be integrated into comprehensive COPD management to improve outcomes and prevent AECOPD.